Research issues in intelligent transportation systems - Figueiredo, Lino (2019)
This paper presents a review of the state of the art on intelligent transportation systems. ITS involves a large number od research areas and, therefore, this paper focus on those we belive to be the most relevant. The main purpose is to study the achievements attained in the last years and to give an overview of possible directions towards future research.